2006
DOI: 10.1007/s00330-006-0254-x
|View full text |Cite
|
Sign up to set email alerts
|

Insertion of virtual pulmonary nodules in CT data of the chest: development of a software tool

Abstract: The purpose of this study was to develop a software tool for the insertion of virtual lung nodules into CT data. Forty software-generated nodules were inserted at random locations and sizes on 20 multi-detector row CT studies of the chest (4 x 1-2.5-mm slice collimation). On each scan, two virtual nodules were inserted. The size, shape, margin and attenuation could arbitrarily vary and were individually adjusted to match real lesions of each patient (real nodules: 6.5+/-3.1 mm; virtual nodules: 6.1+/-3.2 mm). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 22 publications
0
17
0
Order By: Relevance
“…Algorithms have been developed and have been integrated into software tools for automated assessment of nodule volume. Initial studies have shown the value of the volumetry in different settings [14][15][16][17][18][19][20][21][22][23][24]. To our knowledge to date none of the algorithms has been tested on datasets acquired at different MSCT scanners from different vendors.…”
Section: Introductionmentioning
confidence: 99%
“…Algorithms have been developed and have been integrated into software tools for automated assessment of nodule volume. Initial studies have shown the value of the volumetry in different settings [14][15][16][17][18][19][20][21][22][23][24]. To our knowledge to date none of the algorithms has been tested on datasets acquired at different MSCT scanners from different vendors.…”
Section: Introductionmentioning
confidence: 99%
“…A major issue with these approaches to simulated dataset construction is that they lack sufficient biological motivation for their simulated nodule 3-D geometries. Some approaches have involved modeling simulated nodule shapes after real lung nodule data [18][19] , however the goal in these studies has been to create simulated nodules that emulate the characteristics of real nodules, not necessarily the re-construction of the 3-D morphologies of the individual real lung nodules such that they can then be thoroughly manipulated and inserted into new medical images as the simulated nodules. Furthermore, it is important in creating simulated nodule datasets for lung nodules to include a representative proportion of vascularized and juxtapleural nodules that historically have provided the greatest challenge for CAD systems and human readers alike 10,20 .…”
Section: Introductionmentioning
confidence: 99%
“…These lesions are subsequently inserted into the raw projection data or reconstructed clinical images. A few examples of this approach can be found in [17], [18], [19] for lung nodules, in [20], [21] for mammography, and in [22] for digital breast tomosynthesis (DBT). An important factor when using a simulated lesion generated based on mathematical models (rather than biologically inspired models) is to assure the realism of the characteristics of the artificial samples.…”
Section: Introductionmentioning
confidence: 99%